HUBUNGAN KETERLIBATAN KERJA, SEMANGAT KERJA, DAN KOMITMEN ORGANISASI DENGAN KEPUASAN KERJA DOSEN DI POLITEKNIK NEGERI BANJARMASIN - Huwaida, Hikmayanti (Politeknik Negeri Banjarmasin, 2011)
Human resource is one of the most important resources which influence the success of organization. One of important objectives in Human Resources Management is creating employeeâs job satisfaction. Job satisfaction is important thing which lecturers in Banjar-masin State Polytechnic must possess. The higher job satisfaction is, the more possibility to reach organizationâs objective. The objectives of this research are to find out: (1) corre-lation between job involvement and job satisfaction of the lecturers in Banjarmasin State Polytechnic, (2) correlation between morale and job satisfaction of the lecturers in Banjar-masin State Polytechnic, (3) correlation between organization commitment and job satis-faction of the lecturers in Banjarmasin State Polytechnic, (4) correlation among job invol-vement, morale, organization commitment and job satisfaction ofÂ lecturers in Banjarma-sin State Polytechnic.This research is using quantitative approach. Respondents are 123 of 176 lecturers and chosen by using Proportional Random Sampling Techniques. Data are taken with close questionnaire instruments, hypotheses are tested with correlation analysis and descrip-tive analysis with help of SPSS 17.The results of the research show: (1) respondentsâ perception toward job involvement is high enough, perception toward morale is low, perception toward organization commit-ment is high enough, perception toward job satisfactionÂ is low. There are significant cor-relations among: (2) job involvement and job satisfaction of the lecturers in Banjarmasin State Polytechnic, (3) morale and job satisfaction of the lecturers in Banjarmasin State Polytechnic, (4) organization commitment and job satisfaction of the lecturers in Banjar-masin State Polytechnic, (5) job involvement, morale, organization commitment and job satisfaction ofÂ lecturers in Banjarmasin State Polytechnic